2022
DOI: 10.1021/acs.jctc.2c00063
|View full text |Cite
|
Sign up to set email alerts
|

How the Interplay among Conformational Disorder, Solvation, Local, and Charge-Transfer Excitations Affects the Absorption Spectrum and Photoinduced Dynamics of Perylene Diimide Dimers: A Molecular Dynamics/Quantum Vibronic Approach

Abstract: In this contribution we present a mixed quantum-classical dynamical approach for the computation of vibronic absorption spectra of molecular aggregates and their nonadiabatic dynamics, taking into account the coupling between local excitations (LE) and charge-transfer (CT) states. The approach is based on an adiabatic (Ad) separation between the soft degrees of freedom (DoFs) of the system and the stiff vibrations, which are described by the quantum dynamics (QD) of wave packets (WPs) moving on the coupled pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 100 publications
1
37
0
Order By: Relevance
“…We end this section by noting that single QD propagations performed using the averaged explicit solvent parameters shown in Table 1 produce slightly different results to the average over 100 simulations as shown in Figures S7–S12 in the SI, in particular for the Mov GC MM chl and Frz GC QM chl approaches. This is similar to the non‐linear behaviour of the averaged populations with respect to the Hamiltonian parameters some of us have observed for other systems previously [29,33,49] …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…We end this section by noting that single QD propagations performed using the averaged explicit solvent parameters shown in Table 1 produce slightly different results to the average over 100 simulations as shown in Figures S7–S12 in the SI, in particular for the Mov GC MM chl and Frz GC QM chl approaches. This is similar to the non‐linear behaviour of the averaged populations with respect to the Hamiltonian parameters some of us have observed for other systems previously [29,33,49] …”
Section: Resultssupporting
confidence: 88%
“…We followed the numerical procedures used previously, [36] and further details may be found in the SI, Section S1.4. Absorption spectra of GC were calculated via the Fourier transform of the auto‐correlation function produced by the QD calculations, weighted by the diabatic transition dipoles [33,36,56] . Monomeric spectra of G and C were also calculated with auto‐correlation functions produced by QD propagations on LVC models parametrised by PCM(chloroform)/CAM‐B3LYP/6‐31G(d), in the same manner as we have previously done [36,57] .…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported above, this methodology was recently applied to study the photodynamics of AT and GT base pairs, 39 and it promises to be of general applicability. 58 The integration between different techniques is also necessary to simulate the photoactivated dynamics, considering the interplay between elementary processes occurring on very different time scales. The population transfer between the nπ* and ππ* states in the FC region occurs in a few dozens of femtoseconds, but its simulation requires an accurate treatment of the vibronic interactions and makes the inclusion of quantum nuclear effects desirable.…”
Section: ■ the Methodological Approach: Two Eyes Are Better Than Onementioning
confidence: 99%
“…We have shown that such an approach can be also exploited to parametrize generalized LVC Hamiltonians suitable to study at a fully QD level the competition between monomeric and inter-monomeric decay channels in MCAs. As reported above, this methodology was recently applied to study the photodynamics of AT and GT base pairs, and it promises to be of general applicability …”
Section: The Methodological Approach: Two Eyes Are Better Than Onementioning
confidence: 99%